In vitro porphyrin-based photodynamic therapy against mono and polyculture of multidrug-resistant bacteria isolated from integumentary infections in animals - Machado, Carolina S.; Seeger, Marlane G.; Moreira, Kelly S.; Burgo, Thiago A.L. [UNESP]; Iglesias, Bernardo A.; Vogel, Fernanda S.F.; Cargnelutti, Juliana F. (Elsevier, 2022)
Multidrug-resistant (MDR) organisms have been frequently isolated from integumentary lesions of animals, and these lesions are usually infected by more than one pathogen. This study evaluated an in vitro antimicrobial photodynamic therapy (aPDT) using two water-soluble tetra-cationic porphyrins (3-H2TMeP and 4-H2TMeP) against mono and polyculture of MDR bacteria isolated from dogs, cats, and horses. Ten isolates of MDR bacteria (two of each species: Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia marcescens, and Staphylococcus pseudointermedius) were used to evaluate aPDT against the monoculture using a non-cytotoxic concentration of 3-H2TMeP and 4-H2TMeP porphyrins (40 µM), with 30 min of light irradiation in Gram-positive and 90 min for Gram-negative bacteria. The aPDT using the 4-H2TMeP porphyrin was also tested against five different polycultures (Coagulase positive Staphylococcus (CPS) and Pseudomonas sp.; E. coli and Proteus sp.; Pseudomonas sp. and Proteus sp.; CPS and E. coli; and CPS and Proteus sp.) for 90 min. The efficacy of both treatments was evaluated by plating the solution exposed to light or kept in the dark and counting the colonies forming units after 24 h of incubation at 37 °C. Atomic force microscope analysis was used to map bacteria morphological changes and extract adhesion force parameters from the bacteria membranes. Only the 4-H2TMeP porphyrin had antibacterial activity against MDR bacteria in monoculture, especially S. pseudointermedius and P. aeruginosa. In polyculture, the 4-H2TMeP porphyrin reduced bacterial concentrations (p < 0.05) in the associations of E. coli and S. pseudointermedius, P. aeruginosa and S. pseudointermedius, and P. aeruginosa and P. mirabilis. These results showed that aPDT using 4-H2TMeP is a good option for future associations of aPDT and other therapies or in vivo research.
Keywords: AFM analysis; Otitis; Photoinactivation; Skin lesions; Tetra-cationic porphyrin